Multidecadal (1960–2011) shoreline changes in Isbjørnhamna (Hornsund, Svalbard) - Zagórski Piotr; Rodzik Jan; Moskalik Mateusz; Strzelecki Mateusz C.; Lim Michael; Błaszczyk Małgorzata; Promińska Agnieszka; Kruszewski Grzegorz; Styszyńska Anna; Malczewski Artur (Polish Polar Research, 2015)
A section of a gravel-dominated coast in Isbjørnhamna (Hornsund, Svalbard) was analysed to calculate the rate of shoreline changes and explain processes controlling coastal zone development over last 50 years. Between 1960 and 2011, coastal landscape of Isbjørnhamna experienced a significant shift from dominated by influence of tide-water glacier and protected by prolonged sea-ice conditions towards storm-affected and rapidly changing coast. Information derived from analyses of aerial images and geomorphological mapping shows that the Isbjørnhamna coastal zone is dominated by coastal erosion resulting in a shore area reduction of more than 31,600 m2. With ~3,500 m2 of local aggradation, the general balance of changes in the study area of the shore is negative, and amounts to a loss of more than 28,000 m2. Mean shoreline change is −13.1 m (−0.26 m a−1). Erosional processes threaten the Polish Polar Station infrastructure and may damage of one of the storage buildings in nearby future.